Nattaktivitet hos Afrikanska elefanter (Loxodonta africana) i fångenskap med olika kombinationer av miljöberikning - Rönnborn, Sigrid (2014)
African elephants (Loxodonta Africana) are kept all over the world in different kinds of enclosures. The enclosures are however often unsuitable for the elephants. Research has shown that elephants are nocturnal animals. Therefore it is important to keep elephants occupied, for instance by using enrichments, also at the night. Five elephants were studied at Borås djurpark, four elephants in one room and one elephant, named Nyoka, in one room. Behaviours were recorded from 8p.m-6a.m. and behavioural data was observed and collected from videotapes. The elephants were presented with two different kinds of enrichments during four weeks. During week one and three all elephants were presented sticks and haynets with big linkers. During week two and four the group were presented sticks and haynets with small linkers and Nyoka was presented haynets with small linkers and logs.